Dwanaście lat Misyjnej Olimpiady Znajomości Afryki - Puchała, Kinga (Annales Missiologici Posnanienses, 2014)
The article summarizes the short story of a particular scholarly contest addressed to the high school students in Poland. Its theme is the general knowledge of the African continent, from the cultural, sociological, economical, historical and religious point of view. Each edition of the contest had its leading subject. The event met over the past 12 years with great interest among young students across the country and at its central stage in Warsaw was accompanied by various cultural activities aimed at better acquaintance with the richness of the African cultures.